The PID-Based Three Quadcopter UAVs Formation Control under External Disturbance - An, Vo Van; Mien, Trinh Luong (UI Scholars Hub, 2026)
This paper presents the design and evaluation of a formation control strategy for three quadcopter UAVs, based on a PID controller in a leader–follower structure, under the influence of external disturbances. Each UAV employs a six-degree of-freedom dynamic model and utilises a cascade PID control architecture, in which the inner control loop stabilises the attitude. In contrast, the outer control loop regulates position and maintains the formation. The PID parameters are tuned using the Ziegler–Nichols method to ensure simple implementation and low computational cost. The performance of the control system is evaluated through simulations in the MATLAB environment for two typical formation shapes (linear and triangular), both in noise-free conditions and under external disturbances. Simulation results show that in noise-free conditions, the system achieves a rise time of about 2–3 seconds, a settling time of 10–15 seconds for the linear formation, and 20–25 seconds for the triangular formation, with overshoot less than 15% on the position axes and a steady-state error of approximately 0.05 meters. When subjected to external disturbances, the UAVs still maintain the desired formation with a steady-state error of less than 0.1–0.5 meters, demonstrating an acceptable level of disturbance resistance. These results prove that, despite its simple structure, the proposed Leader–Follower PID control strategy can still ensure stable formation and effective trajectory tracking for small-scale UAV systems, while also being suitable for practical applications that require low cost and high deployability.